Neurological disorders associated with glutamic acid decarboxylase 65 antibodies: Clinical spectrum and prognosis of a cohort from China - Bai, Lin; Ren, Haitao; Liang, Menglin; Lu, Qiang; Lin, Nan; Liu, Mange; Fan, Siyuan; Cui, Ruixue; Guan, Hongzhi (Frontiers in Neurology, 2022)
Abstract Objective To describe clinical phenotypes and prognosis of neurological autoimmunity related to glutamic acid decarboxylase 65 (GAD65) antibodies in China. Method In this retrospective observational study from Peking Union Medical College Hospital, we identified patients with neurological disorders related to GAD65 antibodies (cell-based assay) from May 2015 to September 2021. Clinical manifestations, immunotherapy responsiveness, and outcomes were collected after obtaining informed consent from all patients. Results Fifty-five patients were included: 40 (72.73%) were women and initial neurological symptoms developed at 42 (34-55) years of age. The median time to the nadir of the disease was 5 months (range from 1 day to 48 months). The clinical syndromes included limbic encephalitis (LE) or epilepsy (Ep) (n=34, 61.82%), stiff-person syndromes (SPS) (n=18, 32.73%), autoimmune cerebellar ataxia (ACA) (n=11, 20%), and overlap syndrome in 8 (14.55%) patients. Thirty-two (58.2%) patients had comorbidities of other autoimmune diseases, including Hashimoto thyroiditis (n=17, 53.13%), T1DM (n=11, 34.78%), vitiligo (n=6, 18.75%), and others (n=5, 15.63%). Two (3.64%) patients had tumors, including thymoma and small cell lung cancer. Fifty-one (92.7%) patients received first-line immunotherapy (glucocorticoids and/or IV immunoglobulin), and 4 (7.3%) received second-line immunotherapy (rituximab). Long-term immunotherapy (mycophenolate mofetil) was administered to 23 (41.8%) patients. At the median time of 15 months (IQR 6-33.75month, range 3-96month) of follow-up, the patients’ median modified Rankin Score (mRS) had declined from 2 to 1. Thirty-eight (70.4%) patients experienced clinical improvement (mRS declined≥1), 47 (87%) had favorable clinical outcomes (mRS ≤2), and 9 were symptom-free (16.7%). The sustained response to immunotherapy ranged from 7/15 (63.63%) in ACA patients and 22/34 (64.7%) in LE/Ep patients to 14/17 (82.35%) in SPS patients. Conclusions LE/Ep was the most common neurological phenotype of GAD65 antibody neurological autoimmunity in our cohort. Most patients had comorbidities of other autoimmune diseases, but underlying tumors were rare. Most patients responded to immunotherapy. However, the long-term prognosis varied among different clinical phenotypes.